2010
DOI: 10.1139/h09-128
|View full text |Cite
|
Sign up to set email alerts
|

Canadian Society for Exercise Physiology position stand: The use of instability to train the core in athletic and nonathletic conditioning

Abstract: The use of instability devices and exercises to train the core musculature is an essential feature of many training centres and programs. It was the intent of this position stand to provide recommendations regarding the role of instability in resistance training programs designed to train the core musculature. The core is defined as the axial skeleton and all soft tissues with a proximal attachment originating on the axial skeleton, regardless of whether the soft tissue terminates on the axial or appendicular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
117
1
7

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(126 citation statements)
references
References 26 publications
1
117
1
7
Order By: Relevance
“…unstable surface compared to stable surface (Anderson and Behm 2004;Kohler et al 2010;Norwood et al 2007). However, with respect to sport activities and daily functional tasks, a more beneficial training procedure may be to employ standing ground-based free-weight exercises on a stable surface (Behm et al 2010;Hamlyn et al 2007;Nuzzo et al 2008). To our knowledge, this is the first study to investigate the effect of performing the same exercise seated, standing, unilateral and bilateral on core muscle activation.…”
Section: Discussionmentioning
confidence: 98%
“…unstable surface compared to stable surface (Anderson and Behm 2004;Kohler et al 2010;Norwood et al 2007). However, with respect to sport activities and daily functional tasks, a more beneficial training procedure may be to employ standing ground-based free-weight exercises on a stable surface (Behm et al 2010;Hamlyn et al 2007;Nuzzo et al 2008). To our knowledge, this is the first study to investigate the effect of performing the same exercise seated, standing, unilateral and bilateral on core muscle activation.…”
Section: Discussionmentioning
confidence: 98%
“…Thus, it is suggested that a strong and stable trunk, as well as its rapid activation, is beneficial for achieving high sport performances by providing a foundation for greater force production by limbs (Kibler et al 2006;Willardson 2007). On the basis of this idea, exercises aiming to improve trunk stability, i.e., core stabilization exercises, have received remarkable attention in not only rehabilitative, but also athletic fields (Behm et al 2010;Willardson 2007), although a systematic review and meta-analysis revealed that core strength training had large effects on muscle strength but small effects on athletic performance in trained individuals (Prieske et al 2016a).…”
Section: Introductionmentioning
confidence: 99%
“…and mobility, i.e. flexibility [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. In accordance to the needs of field hockey players and coaches, experts agreed that all selected preventive measures (content) should be embedded within the warm-up prior to a field hockey activity (training or match) and made available through a website and an application for smartphone/tablet.…”
Section: The Future Injury Prevention Interventionmentioning
confidence: 99%